The Determination of Metals in Welding Fume by X-Ray-Spectrometry; IOP Conference Series: Earth and Environmental Science; Vol. 115 : Ecology and safety in the technosphere - Kuznetsova O. V.; Begunova L. A.; Romanenko S. V. Sergey Vladimirovich; Solodsky S. A. Sergey Anatolievich (2018, 2018)
Title screen